Pengaruh Keadilan Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan - Hary Nugraha; Rahmad Solling Hamid; Muh. Yusuf Qamaruddin (Penerbit Goodwood, 2024)
Purpose: This study examines the effect of compensation justice and work motivation on improving employee performance in the Perumda Air Minum Tirta Latimojong (PAMTL) Luwu Regency. Methodology/approach: This study was conducted using a survey method with employees at Perumda Air Minum Tirta Latimojong (PAMTL) Luwu Regency and analyzed using multiple linear regression analysis. The sample in this study was taken from 102 people to facilitate the research. Result: The results of this study indicate that compensation justice has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and compensation justice and work motivation simultaneously have a positive and significant effect on employee performance. Limitations: This study was limited to the Perumda Air Minum Tirta Latimojong in Luwu Regency, with a sample of 102 employees. In the research process, the researcher realized that there were respondents who answered not in accordance with the existing reality. Contribution: Research published in the Journal of Management and Organizational Science Studies.